Chernovaty Leonid. Translators’ training: skills and subskills at the source text analysis stage and exercises to develop them - Chernovaty Leonid (Philological Treatises, 2020)
The article deals with the subject matter of translators’ training at the source text analysis stage. The author suggests a list of skills and subskills at the said stage, as well as the exercises to develop them. Mechanisms of compression, paraphrasing, anticipation and skills of reference materials use are reviewed and are suggested to be developed in preparatory exercises.